2009
DOI: 10.20473/j.djmkg.v42.i3.p137-140
|View full text |Cite
|
Sign up to set email alerts
|

Functional relationship of room temperature and setting time of alginate impression material

Abstract: and 31 degrees Celcius room temperatures (n = 5). The initial setting time was tested based on ANSI/ADA Specification no. 18 (ISO 1563). The alginate powder was mixed with distilled water (23/50 ratio), put in the metal ring mould, and the initial setting time was measured by test rod. Data were statistically analyzed by linear regression (a = 0.05). result:The initial setting times were 149. 60 ± 0.55 (control)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The reduced setting time of alginate that has passed its expiration date can be due to external environmental factors, namely moisture contamination and exposure to high temperatures [8,9]. In this study, moisture contamination was possible due to exposure of the alginate material to the air for 24 days.…”
Section: Discussionmentioning
confidence: 90%
“…The reduced setting time of alginate that has passed its expiration date can be due to external environmental factors, namely moisture contamination and exposure to high temperatures [8,9]. In this study, moisture contamination was possible due to exposure of the alginate material to the air for 24 days.…”
Section: Discussionmentioning
confidence: 90%
“…Chemically, prolonged setting process may occur at the early stage of chemical reaction, polymerization stage and gelation stage. Early reaction that takes place since the mixing of alginate powder with water triggers chemical reaction between CaSO 4 with Na 3 PO 4 retarder in the alginate powder, as reaction-1 below: 7 3 CaSO 4 + 2Na 3…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that room temperature without air conditioning, ranging from 24º C-31º C, contributed to alginate's setting time. 3 In such condition, students often need to reduce the amount of alginate powder or add more water than what is recommended by the factory to delay alginate setting time. These methods will reduce mechanical strength of the alginate impression.…”
Section: Introductionmentioning
confidence: 99%